In Situ Surface-Enhanced Raman Spectroscopy Study of the Electrocatalytic Effect of PtFe/C Nanocatalyst on Ethanol Electro-Oxidation in Alkaline Medium - A. C. Gómez-Monsiváis; I. Velázquez-Hernández; L. Álvarez-Contreras; M. Guerra-Balcázar; L. G. Arriaga; N. Arjona; J. Ledesma-García (Energies, 2017)
Currently, the ethanol electro-oxidation reaction has attracted considerable attention in fuel cells because of new green ethanol synthetic methods based on biomass processes that have emerged. In this study, PtFe/C and Pt/C nanoparticles were synthesized by a chemical reduction method and tested in the ethanol electro-oxidation reaction. Furthermore, the electrocatalytic effect of the PtFe bimetallic catalyst was analyzed by in situ surface-enhanced Raman spectroscopy (SERS) coupled to an electrochemical cell. X-ray diffractograms showed typical face-centered cubic structures with crystallite sizes of 3.31 and 3.94 for Pt/C and PtFe/C, respectively. TEM micrographs revealed nanoparticle sizes of 2 ± 0.4 nm and 3 ± 0.6 nm for Pt/C and PtFe/C respectively. PtFe/C exhibited a Pt90Fe10 composition by both X-ray fluorescence and energy-dispersive X-ray spectroscopy. A better electrocatalytic activity as function of concentration was obtained through the incorporation of a small amount of Fe into the Pt lattice and the presence of Fe2+/Fe3+ (observed by X-ray photoelectron spectroscopy). According to SERS experiments, the presence of these iron species promotes the chemisorption of ethanol, the formation of formic acid as main product and renewal of the catalytic sites, resulting in current densities that were at least three fold higher than the values obtained for the Pt/C nanocatalyst.